2015
DOI: 10.1038/srep12692
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial diamond-hexagonal silicon nano-ribbon growth on (001) silicon

Abstract: Silicon crystallizes in the diamond-cubic phase and shows only a weak emission at 1.1 eV. Diamond-hexagonal silicon however has an indirect bandgap at 1.5 eV and has therefore potential for application in opto-electronic devices. Here we discuss a method based on advanced silicon device processing to form diamond-hexagonal silicon nano-ribbons. With an appropriate temperature anneal applied to densify the oxide fillings between silicon fins, the lateral outward stress exerted on fins sandwiched between wide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…1 NWs also allow for the existence of crystal phases that do not even exist in the bulk counterpart. 2,3 Besides non-nitride III-V materials, Si 4,5,6,7,8,9 and Ge 10,11,12 in the NW form can exist in the hexagonal 2H phase (properly named as lonsdaleite), which in the bulk is hardly obtained (usually under high pressure conditions). 13,14 The formation of NWs with hexagonal crystal symmetry has attracted enormous interest among researchers.…”
mentioning
confidence: 99%
“…1 NWs also allow for the existence of crystal phases that do not even exist in the bulk counterpart. 2,3 Besides non-nitride III-V materials, Si 4,5,6,7,8,9 and Ge 10,11,12 in the NW form can exist in the hexagonal 2H phase (properly named as lonsdaleite), which in the bulk is hardly obtained (usually under high pressure conditions). 13,14 The formation of NWs with hexagonal crystal symmetry has attracted enormous interest among researchers.…”
mentioning
confidence: 99%
“…[6][7][8] Nevertheless, in group IV nanowires, the stability of novel polytypes -previously theoretically predicted 9 but experimentally observed only very locally in the form of crystal imperfections [10][11][12][13] is now supported by clear experimental evidences. [14][15][16][17][18][19] For instance, Vincent et al 14 reported the synthesis of quasi-periodic allotrope Ge heterostructures of hexagonal-diamond (wurtzite structure with single atom type) and cubic-diamond domains. These systems were obtained by a straininduced phase transformation in which size effects (in particular the preferential nucleation of dislocations on the wire surface and the activation of unusual slip planes) play a crucial role by lowering the value of the stress required by the cubic to hexagonal transition.…”
mentioning
confidence: 99%
“…At the given oxidation temperature, the oxide is not viscous and is therefore not pushed upwards out of the trench. Hence, the volume expansion leads to a lateral force on the fin sidewalls, [20] leading to a compression of the fins' transverse inplane lattice parameter. In Figure 11 (after STI) one can also identify a bump around À500arcsec which is not related to the multilayer structure but represents compressively strained Si located at the lower part of the fin (below the multilayer structure).…”
Section: Etched Multilayer Finsmentioning
confidence: 99%